Digital Book Development of Belian Traditional Ceremony in Raising Awareness of Local History of High School Students in Pangkalan Kerinci City - Hanifah, Aisyah Nur; Akhyar, Muhammad; Pelu, Musa (Budapest International Research and Critics University, 2021)
This digital book development research aims to see the level of historical awareness of high school students in the city of Pangkalan Kerinci, Pelalawan Regency, Riau Province, towards learning the local history of the Belian Traditional Ceremony, which is one of the medical traditions of the Animism and Dynamism of the Petalangan Tribe. The population of this study was all students Public High School Class 1 in the city of Pangkalan Kerinci, Pelalawan district, Riau province. Consisting of Public High School One Pangkalan Kerinci, Publich High School Two Pangkalan Kerinci, and Public High School of Bernas Pangkalan Kerinci. The sampling technique used is Observation, Interview, Distribution of Questionnaires, Documentation, and Tests. This study uses the Discovery Learning Model, Humanistic Approach, and Content Validity Test with the Aikens method and the Alpha coefficient Reliability Test with the ICC (Interclass Correlation Coeficient) method so as to get accurate and significant results. The results of this study indicate that (1) high school students in the city of Pangkalan Kerinci still lack awareness of local history, (2) history learning media is still very conventional, (3) students' historical awareness of local history preservation is still low and tends to be westernized.